2018
DOI: 10.3892/or.2018.6371
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase, membrane‑associated tyrosine/threonine�1 is associated with the progression of colorectal cancer

Abstract: The protein kinase, membrane‑associated tyrosine/threonine 1 (PKMYT1) is known to inhibit precocious entry into mitosis by phosphorylating CDK1 at Thr14 and Tyr15 residues. However, the functional importance of PKMYT1 in colorectal cancer (CRC) remains unknown. Thus, it is important to elucidate whether PKYMT1 is indispensable in the tumorigenesis of CRC. To investigate the functional importance of PKMYT1 in CRC tumorigenesis, PKMYT1 was knocked down in CRC cell lines such as SW480, SW620, HCT116 and HT29 by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…2 ): (i) the high proliferation rate of cancer cells that follows the activation of driver oncogenes (e.g. RAS, MYC) needs to be sustained by a strong cell cycle regulation machinery; (ii) cancer cells frequently inactivate p53, which is a key gatekeeper of G0/G1 and S phases and, as a consequence, the regulation of cell cycle is sustained entirely by the G2/M checkpoint; (iii) the over-expression of DDR-related kinases is fundamental to maintain a tolerable level of genetic instability, an intrinsic feature of cancer cells [ 31 , 32 ]. Therefore, we can speculate that, once the malignant transformation process has been induced, WEE1 upregulation exerts a pro-tumorigenic functions by securing a tolerable level of genomic instability to cancer cells.…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ): (i) the high proliferation rate of cancer cells that follows the activation of driver oncogenes (e.g. RAS, MYC) needs to be sustained by a strong cell cycle regulation machinery; (ii) cancer cells frequently inactivate p53, which is a key gatekeeper of G0/G1 and S phases and, as a consequence, the regulation of cell cycle is sustained entirely by the G2/M checkpoint; (iii) the over-expression of DDR-related kinases is fundamental to maintain a tolerable level of genetic instability, an intrinsic feature of cancer cells [ 31 , 32 ]. Therefore, we can speculate that, once the malignant transformation process has been induced, WEE1 upregulation exerts a pro-tumorigenic functions by securing a tolerable level of genomic instability to cancer cells.…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
“…WEE1 and PKMYT1 are also over-expressed in solid tumors, including hepatocellular carcinoma, colon cancer, glioblastoma, non-small-cell lung cancer (NSCLS), neuroblastoma, and gastric cancers [ 31 , 32 , 45 – 47 ]. High WEE1 expression has been associated with negative prognostic factors including lymph node involvement, induction of metastasis, increased biomarkers of proliferation (CCND1, Ki67, or CCNA1) and resistance to treatments (radiotherapy or chemotherapy) [ 48 51 ].…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the pathogenesis, diagnosis and treatment of breast cancer remains an area of active investigation 43. This study was the first to investigate the mRNA expression and prognosis of PKMYT1 in breast cancer, although other studies have reported PKMYT1 alternations in the occurrence and development of several cancers, including liver 44 and colorectal carcinomas 45. As the key regulators of G2/M transition, WEE family kinases play essential role in maintaining cell genomic stability under rapid cell proliferation.…”
mentioning
confidence: 98%